(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2023)
The article examines current trends and influence factors in the development of HR branding. Methods for forming a positive image of an organization, a system of measures for the strategic management of an organization, methods for assessing the effectiveness of HR branding in enterprises and a number of other aspects based on foreign experience have been studied and analyzed. In addition, the main stages of the process of branding organizations are described, the development of an organization’s image by identifying and classifying the benefits provided by an HR brand, an analysis of existing approaches to assessing an HR brand, the creation of a system for assessing the economic efficiency of an organization is presented, and recommendations from experts and specialists are presented.